Parametric Study on Suction Caisson Aspect Ratio Under Incline Loading in Sand - Sim , Wei Ping (IRC, 2019)
Suction caisson is widely used in deep water oil and gas platform mooring system, as it has numerous advantageous over other type of underwater foundation system. One of the most significant advantages are suction caisson can be easily installed and retrieved.